Pictorial Riddle Learning Model to Improve Critical Thinking Skills of Fifth-Grade Elementary School Students in Mathematics Learning - Rosliawati, Lia; Aan Yuliyanto; Daminah, Daminah; Fujiarti, Ari (LPPM Universitas Terbuka, 2024)
The research aims to see the improvement of Critical Thinking Skills through pictorial riddle learning. The research method used was classroom action research on mathematics and building cubes and blocks for 21 elementary school students in Pangandaran Regency. The instruments used are observation, tests, interviews, and documentation. This study adopted a quantitative data analysis method, including test sheets measuring students' critical thinking skills and teacher and student observation sheets. Based on the research results, it was found that There was an increase in students' Critical Thinking Skills by using the pictorial riddle learning model, as evidenced by the increase in students' motivation in the learning process, the courage to move forward, students' attention when the teacher explained, the courage to answer questions and student participation in the learning process. This can also be seen from cycle I, with an average score of 74.2 or as many as 10 students who completed out of 21 students with a percentage of (57.1%), then experienced an increase in cycle II with an average of 91.4 or as many as 18 of 21 students completed the percentage (85.7%). The N-Gain criterion value was 0.87>0.7 with high criteria. Thus, the Pictorial Riddle Learning Model can improve students' critical thinking skills in mathematics in elementary schools very well.